Anthropomorphic Capital and Commonwealth Value - Fumagalli, Andrea; Morini, Cristina (Frontiers in Sociology, 2020)
In this essay, we intend to analyze the process of accumulation of contemporary capitalism, in which the regime of valorization derive from the notion of “common” a “ results of social production that are necessary for social interaction and further production, such as knowledges, languages, information affect, and so forth” (Hardt, Negri, 2009) and from its expropriation. When we deal with the concept of "common", the reference is made to a heterogeneous category. In this text we refer to two modalities of expression of the "common": the digital common (section 2) and the common of social reproduction (section 3). Regarding the first case study, the concept of "network value" is investigated and defined as a product of individual life in a relational context increasingly controlled and subsumed by the social media and big data industry. Regarding the second, we discuss how the activity of social reproduction of individuals is today central in the process of accumulation of the economy. “Social reproduction” is a useful concept to investigate what we call the “anthropomorphic capital”, that is the capacity by the contemporary labour organizations to capture and make productive the essence of today’s life and its complexity. In short, it transpires better and better how all activities are productive, i.e. accumulation generators. We observe the apparent paradox of a generalisation of surplus value in the era of the decline of waged employment and with it a tension of capital contemporary to the general mortification of living labour. In fact, we note how capital claims to transform the human being into capital itself, explicitly assuming the whole of human existence as a field from which accumulation can be generated (human being, enterprise or human capital). This is what, at this point, we call anthropomorphic capital or the economy of interiority. In the last section, we report some results of an empirical research “Commonfare-Pie News”, able to underline how life is more and more subsumed to the logic of capitalistic valorization, to the point that today we can speak not only of the subsumption of labour to capital but of a real life subsumption.